A model to predict visual comfort for mobile displays. Issue 6 (2nd September 2022) - Liu, Yu; Zhu, Yuechen; Luo, Ming Ronnier
Abstract: A psychophysical experiment was carried out to investigate visual comfort when reading on three mobile displays at three luminance levels (100, 250 and 500 cd/m 2 ) at five illuminance levels (0, 10, 100, 500 and 1000 lx). Sixty observers including 20 children, 20 young people and 20 elderly people evaluated visual comfort of 42 text‐background combinations using a six‐category point's method. Various effects of lightness contrast, lightness of background, display luminance, and ambient illuminance on visual comfort for the three age groups were revealed. Most interesting, visual comfort is strongly affected by lightness contrast and different ages. A second‐order polynomial regression model is developed to predict visual comfort based on the display settings and ambient illumination at different ages. It could be a valuable tool to design or evaluate display interfaces. Abstract : Visual comfort model based onL* of background (L*background), lightness difference between background and text (L*background ‐L* text), ambient light level and user's age.